Comparing Clinician Ratings of the Quality of Palliative Care in the Intensive Care Unit - Ho, Lawrence A. (2011)
OBJECTIVE: There are numerous challenges to successfully integrating palliative care in the ICU. Our primary goal was to describe and compare the quality of palliative care delivered in an ICU as rated by physicians and nurses working in that ICU. DESIGN: Multi-site study using self-report questionnaires. SETTING: Thirteen hospitals throughout the United States. PARTICIPANTS: Convenience sample of 188 physicians working in critical care (attending physicians, critical care fellows, resident physicians) and 289 critical care nurses. MEASUREMENTS: Clinicians provided overall ratings of the care delivered by either nurses or physicians in their ICU for each of seven domains of ICU palliative care using a 0–10 scale (0 indicating the worst possible and 10 indicating the best possible care). Analyses included descriptive statistics to characterize measurement characteristics of the 10 items, paired Wilcoxon tests comparing item ratings for the domain of symptom management with all other item ratings, and regression analyses assessing differences in ratings within and between clinical disciplines. We used p<0.001 to denote statistical significance to address multiple comparisons. MAIN RESULTS: The ten items demonstrated good content validity with few missing responses, ceiling or floor effects. Items receiving the lowest ratings assessed spiritual support for families, emotional support for ICU clinicians, and palliative-care education for ICU clinicians. All but two items were rated significantly lower than the item assessing symptom management (p<0.001). Nurses rated nursing care significantly higher (p<0.001) than physicians rated physician care in five domains. In addition, while nurses and physicians gave comparable ratings to palliative care delivered by nurses, nurses’ and physicians’ ratings of physician care were significantly different, with nurse ratings of this care lower than physician ratings on all but one domain. CONCLUSION: Our study supports the content validity of the 10 overall rating items and supports the need for improvement in several aspects of palliative care including spiritual support for families, emotional support for clinicians, and clinician education about palliative care in the ICU. Further, our findings provide some preliminary support for surveying ICU clinicians as one way to assess the quality of palliative care in the ICU.